Let's stop feeding the risk monster: towards a social model of 'child protection'. (31st March 2018) - Featherstone, Brid; Gupta, Anna; Morris, Kate; Warner, Joanne
Abstract : This article explores how the child protection system currently operates in England. It analyses how policy and practice has developed, and articulates the need for an alternative approach. It draws from the social model as applied in the fields of disability and mental health, to begin to sketch out more hopeful and progressive possibilities for children, families and communities. The social model specifically draws attention to the economic, environmental and cultural barriers faced by people with differing levels of (dis)ability, but has not been used to think about 'child protection', an area of work in England that is dominated by a focus on risk and risk aversion. This area has paid limited attention to the barriers to ensuring children and young people are cared for safely within families and communities, and the social determinants of much of the harms they experience have not been recognised because of the focus on individualised risk factors.